Comparison Between Antibacterial Extract of Gambier (UncariagambirRoxb) and Chlorhexidine 2% to Enterococcus Faecalis - Sari Dewiyani; Selfina Muthia Sari (Denta Journal Kedokteran Gigi, 2021)
Background: In the case of reinfection after endodontic treatment, Enterococcus faecalis is a bacterium that is commonly found in root canals.  Irrigation was carried out to eliminate Enterococcus faecalis from the root canal. Chlorhexidine 2% irrigating agent was effective in reducing the growth of Enterococcus faecalis bacteria and fungi, but it could not dissolve tissue.  Gambir extract (UncariagambirRoxb) has antioxidant and antibacterial with phenolic content in the form of catechins. Purpose: Describe the antibacterial comparison of  gambier extract (Uncaria gambir Roxb) and 2% chlorhexidine against  Enterococcus faecalis bacteria. Material and Methods: This research is a laboratory experimental research.  Enterococcus faecalis ATCC 29212 is a microbiological sample. Extract of gambier (UncariagambirRoxb) with concentrations of 1%, 1.5%, 2%, 2.5%, and 3%.  2% chlorhexidine solution and a paper disc to measure the inhibition zone were placed on a petri dish containing Mueller-Hinton agar medium, and incubated 1x24 hours.  Gambier extract was made by maceration and rotavapor methods. Results: Gambier extract (UncariagambirRoxb) and 2% chlorhexidine affected the growth inhibition of Enterococcus faecalis bacteria by forming a clear zone around the paper disc in each petri dish. Concentration of 3% is the largest value of the inhibition zone formed in the extract of gambeir (UncariagambirRoxb), while chlorhexidine 2% shows the largest inhibition zone, this can be seen from the average inhibition zone formed of 17.20 mm.Conclussion: There are differences in the antibacterial of gambier extract (UncariagambirRoxb) and 2% chlorhexidine against Enterococcus faecalis bacteria.